A high-resolution patterned HTL thin film, a preparation method thereof and application thereof in high-performance QLED devices

CN122935113APending Publication Date: 2026-10-16HENAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611115163.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而PEDOT:PSS具有酸性且吸水性强,影响器件的长期稳定性,且该方案具有一定的局限性,对于无PEDOT:PSS空穴注入层的器件不适用

Benefits of technology

[0016] This invention introduces Spiro-OMeTAD and the photoinitiator bisFPA into an HTL solution, endowing the HTL solution with photosensitive properties. Based on the cross-linking reaction between TFB and the photoinitiator bisFPA under UV exposure, a special "mesh" structure is formed, within which TFB is solidified, thereby altering the solubility of TFB in the original solution. This successfully develops a novel direct photolithography method for HTL patterning. Using this method, QLED patterned devices and QLED photolithography devices can be further fabricated. This opens up possibilities for QD applications in small-screen displays such as Micro-LEDs and VR/AR glasses, demonstrating significant innovation and practical value. Furthermore, while the cross-linking effect of TFB solution requires the incorporation of bisFPA solution, this can lead to incomplete cleaning of pattern gaps. This invention, by introducing Spiro-OMeTAD, effectively solves this problem, significantly improving the quality of the photolithographic pattern.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122935113A_ABST
    Figure CN122935113A_ABST
Patent Text Reader

Abstract

The application discloses a high-resolution patterned HTL film, a preparation method thereof and application of the high-resolution patterned HTL film in high-performance QLED devices, and belongs to the field of quantum dot (QD) nanotechnology patterned display. The application introduces Spiro-OMeTAD and a photoinitiator bisFPA into an HTL (TFB) solution, so that the HTL solution has photosensitive properties; TFB and the photoinitiator bisFPA are crosslinked by ultraviolet exposure, thereby changing the solubility of TFB in the original solution; the introduction of Spiro-OMeTAD effectively improves the pattern quality and eliminates the TFB residues at the pixel interval; and a novel direct photolithography HTL patterning method is successfully developed. Furthermore, a pixelated blue light QLED device with clear edges is prepared by the method, and the maximum brightness reaches 79818.14 cd / m 2 , and the maximum EQE reaches 3.69%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of patterned display using quantum dot (QD) nanotechnology, specifically relating to a high-resolution patterned HTL thin film, its preparation method, and its application in high-performance QLED devices. Background Technology

[0002] Colloidal quantum dots (QDs) are a class of semiconductor nanocrystals with three-dimensional quantum confinement effects. They possess excellent optical properties such as high luminescent quantum yield (PLQY), narrow emission half-width, tunable emission wavelength, and high color purity, thus being considered one of the most promising luminescent materials for next-generation display technologies. In recent years, with the continuous optimization of quantum dot synthesis processes and device structures, quantum dot display technology has developed rapidly and is widely regarded as a promising candidate to become one of the important display technology routes after organic light-emitting diodes (OLEDs).

[0003] Both quantum dot color conversion layer (QD-CCL) based display technology and direct electroluminescence micro-QLED display technology rely heavily on high-precision patterning manufacturing processes. Currently, the main techniques used in quantum dot patterning include inkjet printing, transfer printing, and photolithography. Inkjet printing offers advantages such as high material utilization and simple processes, but it is susceptible to factors like the coffee ring effect, droplet spreading, and nozzle precision, leading to irregular pattern edges and uneven film thickness, making it difficult to obtain high-resolution and uniform quantum dot patterns. Transfer printing can achieve high-precision pattern deformation, offering advantages in pattern fidelity and processing accuracy, but high-precision alignment between multi-color pixels remains a significant challenge. In contrast, photolithography, after long-term development in the semiconductor manufacturing field, has become the most mature and widely used micro / nano patterning method, combining advantages such as high resolution, large-area fabrication, and excellent consistency. Among them, direct photolithography does not require traditional photoresist as an intermediate layer and can directly pattern the quantum dot light-emitting layer. This effectively reduces the complexity of the process and minimizes the problem of photoresist residue. Therefore, it has become an important research direction for the manufacturing of high-resolution QLED devices in recent years.

[0004] Currently, direct photolithography techniques for patterned QLEDs mainly involve two aspects: patterning of the QD layer or patterning of the hole injection layer PEDOT:PSS. For example, in 2022, Yang et al. (Yang J, Lee M, Park SY, et al. Nondestructive Photopatterning of Heavy‐Metal‐Free Quantum Dots (Adv. Mater.43 / 2022)[J]. Advanced Materials, 2022, 34(43): 2270295.) used branched photodriven ligand crosslinking agents (LiXers) containing multi-azide units to achieve direct photolithographic patterning of heavy metal free quantum dots. The ligand crosslinking is generated by the photochemical reaction of fluorinated benzene azide, and the group is anchored at the end of the n-LiXers. Through the CH insertion reaction, chemical bonds are formed with the aliphatic chains of the adjacent quantum dots under 254nm ultraviolet irradiation. The photocrosslinking strategy can effectively retain the QD film and realize micron-scale RGB quantum dot patterns. Although this method can achieve patterning, it significantly damages the QD (Quantum Diode) for QLED devices, leading to a decline in various photoelectric properties. On the other hand, in 2025, Fan J, Nie L, Tan F, et al. Fabrication of QLED Devices with Designable Patterns via Regulating the Carrier Transport Behavior[J]. Small Methods, 2025, 9(7):2401696., et al. proposed an efficient patterning strategy for fabricating ultra-high resolution QLED devices. By preparing a mixture of photosensitive PEDOT:PSS and an appropriate amount of 2,4-hexanediyne-1,6-diol, the mixture was spin-coated onto an ITO / glass substrate. The resulting film was then photomasked using a self-made 254nm ultraviolet light exposure device, and then developed in deionized water to obtain the designed pattern. Furthermore, by directly photolithography to change its surface morphology, the energy level arrangement and carrier transport channels can be adjusted, thereby optimizing the performance of the photolithography device and improving the performance of red photolithography QLED devices from 17.2% to 18.4%. However, PEDOT:PSS is acidic and highly hygroscopic, which affects the long-term stability of the device. Furthermore, this approach has certain limitations and is not suitable for devices without a PEDOT:PSS hole injection layer.

[0005] Therefore, this application provides a scheme for realizing pixelated QLED devices based on a hole transport layer crosslinking method. On the one hand, the QD layer does not need to undergo rigorous ultraviolet exposure and development steps, effectively preserving the luminescent performance of the QD; on the other hand, this method is universal, independent of the PEDOT:PSS functional layer material, and can be extended to various different hole transport layer materials. By introducing 2,2',7,7'-Tetrakis(N,N-di-p-methoxyphenylamine)-9,9'-spirobifluorene (Spiro-OMeTAD) and ethane-1,2-diyl bis(4-azido-2,3,5,6-tetrafluorobenzoate) (bisFPA) into the hole transport layer Poly[9,9-dioctylfluorene-co-N-(4-butylphenyl)diphenylamine] (TFB), a clear pattern is formed after exposure and development. Among them, the introduction of Spiro-OMeTAD effectively improves the pattern quality and eliminates TFB residue at the pixel spacing. The pixelated device fabricated using this method achieved a maximum brightness of 79818.14 cd / m². 2 The maximum EQE reached 3.69%. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides a high-resolution patterned HTL thin film, its preparation method, and its application in high-performance QLED devices. Utilizing direct photolithography, a solution uniformly mixed with Spiro-OMeTAD and bisFPA is introduced into a TFB solution to impart photosensitive properties. Under room temperature conditions, exposure with a handheld UV lamp induces a cross-linking reaction between TFB and bisFPA, thereby altering the solubility of TFB in the original solution after exposure. Development then enables direct photolithographic patterning of the TFB and Spiro-OMeTAD mixed thin film, resulting in high-resolution and high-precision patterns, and ultimately, the fabrication of high-performance QLED photolithographic devices. The main reaction mechanism lies in the cross-linking reaction between TFB and the azide groups of bisFPA through UV exposure, forming a "mesh" structure that confines the TFB within the exposed area to obtain the desired pattern.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing a high-resolution patterned HTL thin film, the process of which is as follows: (1) Prepare chlorobenzene solutions of TFB, Spiro-OMeTAD, and bisFPA respectively; (2) Add the chlorobenzene solutions of Spiro-OMeTAD and bisFPA to the chlorobenzene solution of TFB, mix well, and make the mass ratio of TFB, Spiro-OMeTAD and bisFPA (35~45): (30~35): (2~4). (3) Spin-coat the solution from step (2) onto the substrate, selectively expose it using a mask and UV, anneal it at 140~160℃ for 25~35 minutes after exposure, develop the exposed substrate, and anneal it at 70~85℃ for 5~15 minutes to obtain a high-resolution patterned HTL film.

[0008] Furthermore, in step (1), the concentrations of the chlorobenzene solution of TFB, the chlorobenzene solution of Spiro-OMeTAD, and the chlorobenzene solution of bisFPA are all 5~10 mg / mL.

[0009] Furthermore, the UV wavelength is 254 nm, and the exposure power density is 0.2 mW / cm². 2 ~100 mW / cm 2 The exposure time is 1 second to 100 hours.

[0010] Furthermore, the developer is 1,3,5-trimethylbenzene.

[0011] The high-resolution patterned HTL film prepared by the above method.

[0012] The application of the aforementioned high-resolution patterned HTL film in high-performance QLED devices involves sequentially fabricating a ZnO layer, a PEDOT:PSS layer, a high-resolution patterned HTL film, a QD light-emitting layer (EML), a ZnMgO layer (ETL), and an aluminum electrode on an ITO glass substrate, followed by encapsulation to fabricate a patterned QLED device.

[0013] Further, the process is as follows: a sol-gel type ZnO with a thickness of 20-40 nm is spin-coated on an ITO glass substrate and annealed at 140-160℃ for 5-15 minutes; a PEDOT:PSS with a thickness of 30-50 nm is spin-coated and annealed at 120-140℃ for 10-20 minutes; a high-resolution patterned HTL film with a thickness of 20-40 nm is prepared by the above preparation method; a QD solution with a thickness of 10-20 nm is spin-coated and annealed at 75-85℃ for 5-15 minutes; an ethanol solution of ZnMgO with a thickness of 20-40 nm is spin-coated and annealed at 55-65℃ for 25-35 minutes; and an aluminum electrode with a thickness of 50-150 nm is vapor-deposited.

[0014] Furthermore, the QD solution is a 15-25 mg / mL blue light CdZnSeS / ZnS solution, and the ethanol solution of ZnMgO has a concentration of 20-30 mg / mL.

[0015] The preparation process of the sol-gel type ZnO is as follows: Zinc acetate dihydrate and ethanolamine are dissolved in 2-methoxyethanol at a molar ratio of 1:1 and stirred at room temperature for 5 to 10 hours. The concentration of zinc acetate dihydrate is 0.5 mmol / mL.

[0016] This invention introduces Spiro-OMeTAD and the photoinitiator bisFPA into an HTL solution, endowing the HTL solution with photosensitive properties. Based on the cross-linking reaction between TFB and the photoinitiator bisFPA under UV exposure, a special "mesh" structure is formed, within which TFB is solidified, thereby altering the solubility of TFB in the original solution. This successfully develops a novel direct photolithography method for HTL patterning. Using this method, QLED patterned devices and QLED photolithography devices can be further fabricated. This opens up possibilities for QD applications in small-screen displays such as Micro-LEDs and VR / AR glasses, demonstrating significant innovation and practical value. Furthermore, while the cross-linking effect of TFB solution requires the incorporation of bisFPA solution, this can lead to incomplete cleaning of pattern gaps. This invention, by introducing Spiro-OMeTAD, effectively solves this problem, significantly improving the quality of the photolithographic pattern. Attached Figure Description

[0017] Figure 1 This is a detailed photolithography flowchart of the photosensitive QD solution prepared in Example 1 and the QD pattern prepared in Example 2 of the present invention; Figure 2 The 150*75 μm TFB:bisFPA crosslinked transport layer pattern prepared in Example 2 of this invention; Figure 3 The 150*75 μm TFB:bisFPA:Spiro-OMeTAD crosslinked transport layer pattern prepared in Example 2 of this invention; Figure 4 This is a structural diagram of the patterned QLED device prepared in Embodiment 3 of the present invention; Figure 5 Photographs of the patterned QLED device and QLED pixel array prepared in Embodiment 3 of the present invention; Figure 6 This is a structural diagram of the patterned QLED device prepared in Example 4 of the present invention; Figure 7 Photographs of the patterned QLED device and QLED pixel array prepared in Embodiment 4 of the present invention; Figure 8 The current density-voltage-luminance (JVL) curve of the patterned QLED device prepared in Example 4 of this invention; Figure 9 The current efficiency (CE)-brightness curve of the patterned QLED device prepared in Example 4 of this invention; Figure 10 The EQE-luminance density curve of the patterned QLED device prepared in Example 4 of this invention; Figure 11 This is the EL emission spectrum of the patterned QLED device prepared in Example 4 of the present invention. Detailed Implementation

[0018] This document will provide a more detailed description of the technical solutions of the present invention in conjunction with specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.

[0019] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available products or can be prepared by known methods.

[0020] Example 1, Photosensitive HTL Mixed Solution In this embodiment, the specific preparation method of the photosensitive HTL mixed solution is as follows: Figure 1 As shown, firstly, 40 mg TFB, 40 mg Spiro-OMeTAD, and 40 mg bisFPA were dissolved in 5 mL of chlorobenzene solution, and the solutions were sonicated and stirred until homogeneous to prepare the original TFB, Spiro-OMeTAD, and bisFPA solutions. Next, 300 μL of TFB solution was taken and 12.5 μL of bisFPA solution was added, mixed, and stirred until homogeneous to obtain the first photosensitizing HTL mixed solution. Simultaneously, 200 μL of TFB solution was taken and 160 μL of Spiro-OMeTAD solution and 15 μL of bisFPA solution were added sequentially, mixed, and stirred until homogeneous. Finally, the desired second photosensitizing HTL mixed solution was obtained.

[0021] Example 2: Fabrication of patterned HTL thin films like Figure 1 As shown, the photosensitive HTL mixed solution prepared in Example 1 was uniformly spin-coated onto the surface of a glass substrate to form a transparent film of uniform thickness. Then, a photomask was tightly attached to the glass substrate, and a handheld UV lamp with a wavelength of 254 nm was used at a power density of 1 mW / cm². 2UV exposure was performed with an exposure time of 2 minutes, followed by annealing at 150°C for 30 minutes. Finally, the exposed glass substrate was developed using trimethylbenzene as the developer and annealed at 80°C for 10 minutes to obtain the desired patterned HTL film. Figure 2 and Figure 3 ). Figure 2 The TFB:bisFPA crosslinked transport layer pattern with a spacing of 50 μm and a pixel size of 150*75 μm prepared in Example 2 of the present invention; Figure 3 The TFB:bisFPA:Spiro-OMeTAD crosslinked transport layer pattern with a spacing of 50 μm and a pixel size of 150*75 μm prepared in Example 2 of this invention; Figure 2 and Figure 3 It can be seen that, compared with the TFB:bisFPA crosslinked transport layer pattern, the patterned film mixed with Spiro-OMeTAD has clearer edges and no quantum dot residue at the pixel spacing.

[0022] Example 3: Fabrication of a patterned QLED device based on a TFB:bisFPA crosslinking transport layer First, the 2.54cm×2.54cm ITO glass substrate was ultrasonically washed for 15 minutes each with a washing solution, ultrapure water, acetone and isopropanol to make its surface clean and free of impurities. Then, the washed ITO glass substrate was ozone-treated for 15 minutes, followed by spin-coating of 30 nm sol-gel ZnO in air and annealing at 150°C for 10 minutes. The sol-gel ZnO was prepared by mixing 220 mg zinc acetate dihydrate, 61 μL ethanolamine, and 2 mL 2-methoxyethanol, and stirring at room temperature for 8 hours. Next, a 40 nm thick PEDOT:PSS (AI 4083, purchased from Heraeus Deutschland) was spin-coated and annealed at 130°C for 15 minutes. After cooling, the first photosensitive HTL mixed solution (TFB:bisFPA, 30 nm) prepared in Example 1 was spin-coated. Using the direct photolithography method of Example 2, selective exposure was performed through a mask and a handheld UV lamp. After exposure, annealing was performed at 150°C for 30 minutes, followed by development with trimethylbenzene to obtain the desired HTL patterned hole transport layer (pixel 150*75 μm, spacing 50 μm). The device was then spin-coated with a 15 nm thick layer of blue CdZnSeS / ZnS QD solution (concentration 20 mg / mL) and annealed at 80 °C for 10 minutes. Next, a 30 nm thick layer of ZnMgO (solvent ethanol, concentration 25 mg / mL) was spin-coated and annealed at 60 °C for 30 minutes. Finally, an aluminum (100 nm) electrode was deposited, acrylic adhesive was applied to the device, a glass slide was placed on top, and the device was cured by irradiation with a 365 nm UV lamp for 30 seconds. This yielded a patterned QLED device based on a TFB:bisFPA crosslinked transport layer, as shown in the diagram. Figure 4 As shown, from bottom to top, it includes an ITO substrate, a ZnO layer, a PEDOT:PSS layer, a TFB:bisFPA crosslinking transport layer, a QD luminescent layer (EML), a ZnMgO layer (ETL), and an aluminum electrode. Figure 5 These are photographs of the patterned QLED device and QLED pixel array prepared in Example 3. Figure 5 It can be seen that there is obvious light emission phenomenon in the pixel spacing of the obtained device pattern, which makes the pixelated device pattern look like an inverted pattern. This is mainly attributed to the presence of TFB residue at the pixel spacing of the TFB:bisFPA film.

[0023] Example 4: Fabrication of a patterned QLED device based on a TFB:bisFPA:Spiro-OMeTAD crosslinked transport layer First, the 2.54cm×2.54cm ITO glass substrate was ultrasonically washed for 15 minutes each with a washing solution, ultrapure water, acetone and isopropanol to make its surface clean and free of impurities. Then, the washed ITO glass substrate was subjected to ozone treatment for 15 minutes, followed by spin-coating of 30 nm sol-gel ZnO in air. The preparation method of the sol-gel ZnO was the same as in Example 3. The substrate was then annealed at 150°C for 10 minutes. Next, a 40 nm thick PEDOT:PSS (AI 4083, purchased from Heraeus Deutschland) was spin-coated and annealed at 130°C for 15 minutes. After cooling, the second photosensitive HTL mixed solution (TFB:bisFPA:Spiro-OMeTAD, 30 nm) prepared in Example 1 was spin-coated. Using the direct photolithography method of Example 2, selective exposure was performed through a mask and a handheld UV lamp. After exposure, the substrate was annealed at 150°C for 30 minutes, followed by development with trimethylbenzene to obtain the desired patterned hole transport layer (pixel 150*40 μm, spacing 50 μm), and annealed at 80°C for 10 minutes. After cooling, a 15 nm thick layer was spin-coated. A blue CdZnSeS / ZnS QD solution (concentration 20 mg / mL) was prepared and annealed at 80℃ for 10 minutes. Then, 30 nm of ZnMgO (ethanol solvent, concentration 25 mg / mL) was spin-coated and annealed at 60℃ for 30 minutes. Finally, aluminum was deposited by vapor deposition (100 nm), acrylic adhesive was applied to the device, a glass slide was placed on top, and the device was cured by irradiation with a 365 nm UV lamp for 30 seconds to obtain a patterned QLED device. The structure is shown below. Figure 6 As shown, from bottom to top, the pattern includes an ITO substrate, a ZnO layer, a PEDOT:PSS layer, a TFB:bisFPA:Spiro-OMeTAD crosslinking transport layer (HTL), a QD emitting layer (EML), a ZnMgO layer (ETL), and an aluminum electrode. The resulting device pattern has pixels that do not emit light, indicating a positive pattern. Performance testing was conducted on this patterned device. Various performance parameters (external quantum efficiency (EQE), luminance, current density, current efficiency (CE), etc.) and its EL emission spectrum of the patterned QLED device were obtained using a marine optical spectrometer (USB2000, relative irradiation mode) and a Keithley 2400 source meter. The maximum EQE was 3.69%, the maximum CE was 4.33 cd / A, and the maximum luminance reached 79818.14 cd / m². 2 .

[0024] Figure 7 Photographs of the patterned QLED device and QLED pixel array prepared in Embodiment 4 of the present invention; Figure 8The current density-voltage-luminance (JVL) curve of the patterned QLED device prepared in Example 4 of this invention is shown below. Figure 8 As can be seen, the JVL characteristic curve exhibits typical diode characteristics, turning on at 2.7V and reaching its maximum brightness of 79818.14 cd / m² at 6.5V. 2 .

[0025] Figure 9 The current efficiency (CE)-luminance curve of the patterned QLED device prepared in Example 4 of this invention is shown below. Figure 9 It can be seen that the brightness is 28796.3 cd / m². 2 At that time, the device reached its maximum CE, which was 4.33 cd / A.

[0026] Figure 10 The EQE-brightness curve of the patterned QLED device prepared in Example 4 of this invention is obtained from... Figure 10 It can be seen that at a current density of 663.8 mA / cm² 2 At that time, the device's EQE was at its maximum, at 3.69%.

[0027] Figure 11 The EL emission spectrum of the patterned QLED device prepared in Example 4 of this invention is shown by... Figure 11 It can be seen that the peak wavelength is 487.88nm, the half-width is about 28.58nm, and the shape and peak position of the EL spectrum of the device do not change when the applied voltage is increased from 3V to 8V.

[0028] The embodiments of the present invention have been described above. However, the present invention is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a high-resolution patterned HTL thin film, characterized in that, The process is as follows: (1) Prepare chlorobenzene solutions of TFB, Spiro-OMeTAD, and bisFPA respectively; (2) Add the chlorobenzene solutions of Spiro-OMeTAD and bisFPA to the chlorobenzene solution of TFB, mix well, and make the mass ratio of TFB, Spiro-OMeTAD and bisFPA (35~45): (30~35): (2~4). (3) Spin-coat the solution from step (2) onto the substrate, selectively expose it using a mask and UV, anneal it at 140~160℃ for 25~35 minutes after exposure, develop the exposed substrate, and anneal it at 70~85℃ for 5~15 minutes to obtain a high-resolution patterned HTL film.

2. The method for preparing a high-resolution patterned HTL thin film according to claim 1, characterized in that, In step (1), the concentrations of the chlorobenzene solutions of TFB, Spiro-OMeTAD, and bisFPA are all 5~10 mg / mL.

3. The method for preparing the high-resolution patterned HTL thin film according to claim 1, characterized in that, The UV wavelength is 254 nm, and the exposure power density is 0.2 mW / cm². 2 ~100 mW / cm 2 The exposure time is 1 second to 100 hours.

4. The method for preparing a high-resolution patterned HTL thin film according to claim 1, characterized in that, The developer is 1,3,5-trimethylbenzene.

5. A high-resolution patterned HTL film prepared by the preparation method according to any one of claims 1 to 4.

6. The application of the high-resolution patterned HTL thin film of claim 5 in high-performance QLED devices, characterized in that, A patterned QLED device is fabricated by sequentially preparing a ZnO layer, a PEDOT:PSS layer, a high-resolution patterned HTL film, a QD light-emitting layer, a ZnMgO layer, and an aluminum electrode on an ITO glass substrate, and then encapsulating it.

7. The application according to claim 6, characterized in that, The process is as follows: a sol-gel type ZnO with a thickness of 20-40 nm is spin-coated onto an ITO glass substrate and annealed at 140-160°C for 5-15 minutes; a PEDOT:PSS with a thickness of 30-50 nm is spin-coated and annealed at 120-140°C for 10-20 minutes; a high-resolution patterned HTL film with a thickness of 20-40 nm is prepared by the preparation method described in any one of claims 1 to 4; a QD solution with a thickness of 10-20 nm is spin-coated and annealed at 75-85°C for 5-15 minutes; an ethanol solution of ZnMgO with a thickness of 20-40 nm is spin-coated and annealed at 55-65°C for 25-35 minutes; and an aluminum electrode with a thickness of 50-150 nm is vapor-deposited.

8. The application according to claim 7, characterized in that, The QD solution is a 15-25 mg / mL blue light CdZnSeS / ZnS solution, and the ZnMgO ethanol solution has a concentration of 20-30 mg / mL.